A study on BRAC's Palli Shamaj - Rashid, Ahmed Tareq; Alim, Md. Abdul (BRAC Research and Evaluation Division (RED), 2019)
Palli Shamaj is a ward-level organization consisting of representatives from several village organizations of BRAC and outside poor members. The study aims to depict a regional density mapping of geographical distribution of Palli Shamaj and their activities and the number of elected Palli Shaamaj members in union parishad elections. Data were collected from 9,440 Palli Shamaj from 55 regions of BRAC. The density mapping, measured at different administrative levels, shows that Rajshahi division not only has the highest number of Palli Shamaj but also the highest density in proportion to the number of wards. No significant regional variation was observed with regard to Palli Shamaj activities in acquiring different types of government services (VGF and VGD cards, old-age and widow allowances) as well as participation in social activities such as participation in shalish, conflict resolution, preventing polygamy, and early marriage. It was found that Palli Shamaj members have won 13% and 1.6% of the total reserved and general seats respectively. The findings indicate that there is a link between activities of Palli Shamaj and the participation of Palli Shamaj members in local government elections.